Auditor Performance Perspective: Role Conflict and Due Professional Care - Ely Suhayati; Xepi Twinarti; Ahmad Muhammad Oroji (Australasian Accounting, Business and Finance Journal, 2024)
A decline in auditor performance has become a public concern, particularly due to the auditors’ involvement in Role Conflict and Due Professional Care during audits. The objective of this research is to determine the extent to which role conflict influences auditor performance and the extent to which due professional care impacts auditor performance. The research method employed is descriptive verification with a quantitative approach using multiple linear regression analysis through the Pearson product moment, and data collection techniques with questionnaires tested using SPSS 23.0 for Windows software. The results of this study indicate that role conflict and due professional care influence auditor performance, meaning if the auditor can manage existing conflicts well and is able to use professional skills, then Auditor Performance will increase. Similar research results also occurred in Iran and the United States, where auditor performance declined due to the lack of spiritual intelligence of auditors and communication modes. The novelty of this research is that auditor performance declines due to different roles that must be performed simultaneously, resulting in role conflict when conducting an examination that violates due professional care. This research underlines that if role conflict can be minimized and due professional care increases, then auditor performance will also increase.
Keywords: Auditor Performance; Role Conflict; Due Professional Care